INFLUENCE OF RAW MILK QUALITY ON THE EXPORT CAPACITY OF THE DAIRY SECTOR IN UKRAINE - IBATULLIN, Ildus; KARPENKO, Vitalii; STRIKHOVSKYI, Dmytro; ANDRUSHKO, Vitaly (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article explores the impact of raw milk quality on the export potential of Ukraine’s dairy industry in the context of agrarian sector transformation, standard harmonization, and integration into the global market. The study emphasizes that the quality of raw milk is a key factor in the development of a competitive export-oriented product, particularly for demanding markets such as the European Union, the Gulf countries, North Africa, and Asia. The dynamics of extra grade milk production are analyzed, and the main internal barriers to quality improvement are identified – including inadequate primary cooling infrastructure, a lack of local laboratory control, and weak cooperation among small producers. The role of government regulation, institutional support, and industry associations in the modernization of dairy production is examined. Special attention is given to the implementation of standards aligned with the requirements of the Codex Alimentarius, HACCP, ISO, as well as the EU regulations on microbiological criteria and residue levels. It is argued that only a systematic approach to ensuring high-quality raw milk – from improved on-farm management to the control of logistics stages – can guarantee sustainable export growth. Several strategic directions are proposed, including the strengthening of veterinary control, development of laboratory networks, financial support for the modernization of primary production, and the consolidation of production units through cooperation. The study concludes that improving raw milk quality has a multiplier effect – enhancing the economic performance of producers, contributing to a positive image of Ukrainian dairy products, and ensuring long-term export presence in international markets.